PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA - Purnama, Dendi (Jurnal Riset Keuangan dan Akuntansi, 2017)
This study aims to analyze the effect of profitability, leverage, firm size, institutional ownership and managerial ownership of earnings management. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange from 2010 to 2015. The sample in this study as many as 47 companies for 6 years.The result of analysis shows that profitability have a significant positive effect to earnings management, firm size and managerial ownership negatively affect earnings management, while leverage and institutional ownership have no effect to earnings management. While jointly shows that the variable profitability, firm size, leverage, institutional ownership and managerial ownership have a significant effect on earnings management. Keywords: Profitability, Leverage, Company Size, Institutional Ownership, Managerial Ownership and Profit Management,